Faktor-kaktor Penyebab Kemiskinan Kultural dan Model Pengentasan Berbasis Kearifan Lokal: Studi pada Masyarakat Miskin di Pegunungan Kintamani, Bali - Made Kerta Adhi; I Ketut Ardana; I Made Maduriana (Pusat Kajian Bali Universitas Udayana, 2016)
This study aims to determine the main factors leading causes of cultural poverty and developing poverty aleviation model based on local wisdom, such as Hindu based-philosophy Tat Twam Asi (if I were you) in the community of Kintamani tourist area. The objectives acomplishment of the study were carried out by using the paradigm prototypical studies, combined with reflective analysis method. It was found that the main factors causing poverty in certain parts of Kintamani community were cultural values ??that lead them difficult to reduce the poverty, such as the cultural habit of begging, laziness, pessimistic, easy to quit, lack of motivation, resigned to fate family situation that been poor hereditary, and low education level. Poverty alleviation model was proposed by elaborating Tat Twam Asi values in the community of Kintamani tourist area through functionalization of social and culture institutions.